2022
DOI: 10.15244/pjoes/146739
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chlorophyll Fluorescence and Growth Responses of two <i>Amaranthus</i> Species to Increased N Supply Variability

Abstract: Alien plant invasion attracts increasing attention from ecologists [1-2], as it is posing profound negative impacts and challenges on ecosystem balance and human society's healthy development [3][4]. This event is mainly caused by the introduction of exotic species to a new habitat. However, how to exactly predict and control plant invasions always perplexes most researchers [5]. Normally, invasive plants are highly possible to meet their congeners in a novel environment since they have similar ecological nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…growth and yield of amaranth crops. Wang et al (2022) indicated high N supply with a pattern of variability, rather than consistency, stimulated a higher plant height and more DM in A. palmeri. Therefore, HN with temporal variability supply might also promote plant growth of A. viridis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…growth and yield of amaranth crops. Wang et al (2022) indicated high N supply with a pattern of variability, rather than consistency, stimulated a higher plant height and more DM in A. palmeri. Therefore, HN with temporal variability supply might also promote plant growth of A. viridis.…”
Section: Discussionmentioning
confidence: 92%
“…Recent research suggests that moderate N fertilization promotes agronomic traits and yield in the amaranth crop (Maseko et al 2019). In addition, a high N supply with temporal variability might increase plant growth dramatically (Wang et al 2022). On the other hand, the accumulation of secondary metabolites, such as phenols, Flv, and their related derivatives in crops also responds to N application (Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen (N) and phosphorus (P) are essential macronutrients for plant growth and development, and they are also nutrients that most frequently limit primary productivity in all ecosystems in the biosphere (Aerts and Chapin 1999, Hall et al 2005, Elser et al 2007, Chen et al 2022. Previous studies have shown that N and P deficiencies cause negative effects on plants (Zhang et al 2014a, Wang et al 2022a; photosynthesis always decreases under N and P deficiencies (Zhang et al 2014a,b;Luo et al 2016). As a vital constituent in proteins, nucleic acids, chlorophylls, and many secondary metabolites of plants (Luo et al 2013), N plays an essential role in the enzymatic activities of photosynthetic processes (Güsewell, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…P deficiency not only reduces the photosynthetic capacity of leaves (Neocleous and Savvas 2019) but also causes the premature development of plant reproductive organs and inhibition of stem and leaf growth (Sun et al 2021). However, the responses of photosynthesis, chlorophyll (Chl) fluorescence, accumulation of secondary metabolites, and growth in plants to N and P applications are species-or genotypespecific (Zhang et al 2014a, Deng et al 2019, Zhao et al 2021, Wang et al 2022a.…”
Section: Introductionmentioning
confidence: 99%
“…Amaranthus palmeri (A. palmeri), a dioecious annual weed of the family Amaranthaceae, is native to the southwestern United States to northern Mexico, and then invaded all over the world. It is now widely distributed among Europe, Oceania and Asia [15]. A. palmeri is one of the main agricultural weeds in America, which could lead to the letdown of crop yield by 63~91% [16].…”
Section: Introductionmentioning
confidence: 99%